Occurrence, site fidelity, and associations of oceanic common bottlenose dolphins (Tursiops truncatus) off northeastern New Zealand. Issue 4 (4th July 2020) - Zaeschmar, Jochen R.; Tezanos‐Pinto, Gabriela; Dwyer, Sarah L.; Peters, Catherine H.; Berghan, Jo; Donnelly, David; Meissner, Anna M.; Visser, Ingrid N.; Weir, Jody S.; Judkins, Alastair G.; Brough, Tom; Guerra, Marta; et al.
Abstract: Two ecotypes of the common bottlenose dolphin ( Tursiops truncatus ) occur in New Zealand waters: a widely studied Nationally Endangered coastal ecotype and a little‐known oceanic ecotype. Site fidelity and association patterns of the oceanic ecotype, and home range overlap with the coastal ecotype, are examined from photo‐identification records collected off northeastern New Zealand between 2005 and 2016. The oceanic ecotype occurs widely in the study area: distance from shore ranged from <1 to ~150 km and home ranges of the two ecotypes overlap in some areas. Forty‐nine percent of the 478 identified distinctive or very distinctive individuals were sighted during more than 1 year and resightings spanned over 10 years and 650 km. All individuals were linked by association in a single, albeit clustered, social network. Unlike the coastal ecotype, interspecific associations with false killer ( Pseudorca crassidens ) and southern long‐finned pilot whales ( Globicephala melas edwardii ) were frequent, occurring during 84% of encounters. Only one oceanic individual matched any of the individuals from the coastal ecotype photo‐identification catalogues throughout the study area, suggesting that the two ecotypes co‐occur parapatrically. We recommend that the two ecotypes be considered independent management units for conservation purposes due to their divergent ecologies.